2020
DOI: 10.1002/joe.22001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trust in leadership on organizational transformation

Abstract: During periods of transformation or in other uncertain and volatile business environments, high levels of work engagement-the extent to which employees identify with their role in an organization-enable leaders to implement change more effectively. A study conducted in Bangladesh's banking sector explores the influence of transformational leadership on work engagement and examines the mediating effect of trust in that relationship. Taking place in a context of significant organizational change, the study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 66 publications
4
51
0
2
Order By: Relevance
“…Bangladesh's banking sector has been going through a major transition process to compete in competitive global markets and meet customers' demands. The banking sector is described as facing a slow‐motion crisis (Islam et al., 2020a; Regi & Golden, 2019). The immediate challenges facing the banking sector are upgrading their product line‐up, modernization, and the development of a suitable IT infrastructure.…”
Section: The Banking Sector In Bangladeshmentioning
confidence: 99%
See 4 more Smart Citations
“…Bangladesh's banking sector has been going through a major transition process to compete in competitive global markets and meet customers' demands. The banking sector is described as facing a slow‐motion crisis (Islam et al., 2020a; Regi & Golden, 2019). The immediate challenges facing the banking sector are upgrading their product line‐up, modernization, and the development of a suitable IT infrastructure.…”
Section: The Banking Sector In Bangladeshmentioning
confidence: 99%
“…Further challenges are posed by the growth of artificial intelligence, the development of green banking models, and enriched banking supervision methods. Research has shown that some banks in Bangladesh are failing to deal with these challenges (Islam et al., 2020a). The 2019 Global Competitiveness Index reported that the banking sector in Bangladesh had the worst performance among all the countries in South Asia (Schwab, 2019).…”
Section: The Banking Sector In Bangladeshmentioning
confidence: 99%
See 3 more Smart Citations